Role of Local Governments in Managing Mangrove Damage: The Manokwari Case - Maskun; Hasbi As Siddiq; Enny Martha Sasea (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Mangrove ecosystems are known as forests that are able to live adapt to extreme coastal environments such as changing salinity (2-22 ‰ to reach 38 ‰), but the existence of mangrove ecosystems is vulnerable to environmental changes, such as wind, erosion and abrasion. Changes in the environment are caused by ecological pressure that comes from nature and humans. Forms of ecological pressure originating from humans are generally associated with the use of mangroves such as land conversion for settlements, fishponds, and tourism. The development of mangrove forests in Kabupaten Manokwari requires the attention of the government and the community, because the lack of public awareness and coordination between agencies will greatly influence the preservation of mangrove forests, especially the damage to ecosystems in mangrove forest areas.